ANALYSIS OF BUSINESS SUCCESS OF CAFE IN TULUNGAGUNG: A PHENOMENOLOGICAL STUDY OF CAFE TAJUG TULUNGAGUNG - Wahyu Kawitaning Kinasih; Cipto Wardoyo; Madziatul Churiyah (Yayasan Education and Social Center, 2022)
Business success is defined as increased sales over previous results. A company's primary goal is business success, with all of its activities aimed at achieving success. This study employs qualitative research methods with a phenomenological analysis approach. The researcher focuses on a person's phenomenon or life experience in running a business. The phenomena revealed include why entrepreneurs start a business, how they measure the success of their business, and how entrepreneurs keep their business running. The participants in this study are the owners, employees, and customers of Cafe Tajug Tulungagung. The study results found that: 1) The business owner wanted to open a Cafe Tajug business because he wanted to innovate more than his previous business. Business owners want to create jobs and open businesses in the same field but with different concepts and themes. 2) How to measure business success, the owner of Cafe Tajug uses indicators including innovation, development, financial, non-financial, customer satisfaction, and employee satisfaction. 3) In maintaining the business, the owner of Cafe Tajug constantly innovates whenever there are new ideas, carries out business development, collaborates with investors, pays attention to employee welfare, gets motivation and support from family, and pays attention to customer satisfaction so that profit targets are always achieved